RADIOPROTECTIVE EFFECT OF RAMSON (ÁLLIUM URSÍNUM L.) AND BOG BILBERRY (VACCINIUM ULIGINOSUM L.) - Tarabanko, Valery E.; Rodionov, Evgeniy T.; Toporkova, Ludmila B.; Sergey, Muench; Orlovskaya, Irina A. (Химия растительного сырья, 2015)
Radioprotective properties of the products produced from ramson (Állium Ursínum L.) and bog bilberry (Vaccinium uliginosum L.) were studied. Mice fed with the dried ramson and the bog bilberry extract were irradiated by X-rays (8 Gray). Strong radioprotective effect of these plant products was registered. The ramson demonstrated more radioprotective effect in comparison with bog bilberryextract. The radioprotective effect of Allium is probably determined by cysteine sulfoxides and their degradation products, such as diallyl disulfide and allyl methyl disulfide. The radioprotectors studied increase minimum parameters of erythropoiesis (red blood cell number and hematocrit) by a factor 1,5. Rapid recovery of the parameter of the platelets number of peripheral blood in all groups in comparison with control was registered. The survival ofmice fed with the dried ramson and the bog bilberry extract increased up to 60 and 53%, correspondingly, in comparison with 6,7%in the control group. These substances do not have side effects and contraindications and may be considered as a promising radioprotectors.